Is Arabic Rhetoric the Same as Rhetoric? A Reading of Concepts and Content - belkheir, refice; ghilous, salah (El Omda in Linguistics and Discourse Analysis, 2025)
This article attempts to investigate a terminological issue of whether Arabic rhetoric is Greek rhetoric After research and investigation, the research concluded that Arabic rhetoric differs radically from Greek rhetoric, whether in terms of terminology or in terms of scientific meaning. We found that translating it into rhetoric is the safest, and in no way can it be accepted to translate it into rhetoric, because of the unfairness in that. The right to eloquence, a violation of its contents, and a reduction of its chapters